EFFORTS TO IMPROVE TEACHER COMPETENCE IN MEDIA DEVELOPMENTLEARNING APPLICATION BASED CANVA VIA ACTIVITY KKG MINI - Noralita; Akmaluddin; Siti Mayang Sari; syarfuni (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study emphasizes increasing teacher competency in media development canva-based learning with the implementation of Mini KKG activities at SDN 2 Tijue. Study This is Study Action School (PTS) with four step tree, that is: action planning, action implementation, observation and reflection. The research subjects were 10 Class teacher at SDN 2 Tijue . Data collection techniques using observation and documentation techniques. Deep data analysis method study This use analysis data qualitative. Based on results study can conclusion that implementation of the Mini KKG proven capableincreasing teacher competence in developing Canva-based learning media. Matter this is evidenced by the increase in the results of the competency assessment of teachers at SDN 2 Tijue in development media learning based canvas in where on condition beginningthe average value is 45.60 and is included in the Less (K) category, increasing in the first cycle with average mark 70,47 And enter in category Enough © And on cycle second with average mark91.58 and included in the Good category (B). As for increasing the competence of teachers at SDN 2 Tijue in developing Canva-based learning media individually in the initial conditions there were no teachers who were declared complete, in the first cycle 10 teachers or 91.58%stated complete And on cycle second 10 teachers or 100% declared complete.